2015
DOI: 10.1093/hmg/ddv460
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genetic background on the dystrophic phenotype inmdxmice

Abstract: Genetic background significantly affects phenotype in multiple mouse models of human diseases, including muscular dystrophy. This phenotypic variability is partly attributed to genetic modifiers that regulate the disease process. Studies have demonstrated that introduction of the γ-sarcoglycan-null allele onto the DBA/2J background confers a more severe muscular dystrophy phenotype than the original strain, demonstrating the presence of genetic modifier loci in the DBA/2J background. To characterize the phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
261
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(287 citation statements)
references
References 34 publications
24
261
1
1
Order By: Relevance
“…Coley et al ., have recently reported that mdx -DBA exhibits impaired skeletal and cardiac muscle functions at an earlier age than mdx -B1034. We also previously reported that compared to mdx -B10, mdx -DBA mice showed the greater decrease in skeletal muscle function and weight, and increased accumulation of fat and fibrosis, but did not show increased muscle degeneration29.…”
Section: Discussionmentioning
confidence: 70%
“…Coley et al ., have recently reported that mdx -DBA exhibits impaired skeletal and cardiac muscle functions at an earlier age than mdx -B1034. We also previously reported that compared to mdx -B10, mdx -DBA mice showed the greater decrease in skeletal muscle function and weight, and increased accumulation of fat and fibrosis, but did not show increased muscle degeneration29.…”
Section: Discussionmentioning
confidence: 70%
“…However, there has been limited widespread uptake of weekly steroid regimens, so we investigated the effects of weekly and daily steroid dosing in an animal model of muscular dystrophy. These studies were conduced in 6-month-old mdx male mice on a DBA/2J background, since these mice bear a closer resemblance to human DMD pathology and specifically the age at which steroid dosing is often initiated (36). Mice were given prednisone and deflazacort i.p.…”
Section: Resultsmentioning
confidence: 99%
“…There are several other mouse models of muscular dystrophy, for example D2‐ mdx (Coley et al . ) and mdx 4cv /mTR G2 (Yucel et al . 2018), which purportedly better recapitulate the human dystrophinopathies at least for limb and cardiac muscle.…”
Section: Discussionmentioning
confidence: 99%